Advanced vehicle technology - Heisler, Heinz (Oxford : Butterworth-Heinemann, 2002)
This eagerly awaited second edition of Heinz Heisler's Advanced Vehicle Technology is a comprehensive and thorough description of vehice bodies and components. The second edition has been rigorously updated to provide additional material on subjects such as antilock braking, vehicle aerodynamics, tire tread design advances, electronically controlled anti-vibration engine mountings and transport refrigeration. Around 100 new diagrams have been included to complement the text. Advanced Vehicle Technology 2nd edition's depth of coverage, detailed illustrations and fluent and precise style are the outstanding features in this high quality student text. More quality artwork has been added to enhance and add value to the explanation given in the text. 16 key topics have been updated to bring this 2nd edition in line with current technology. Fully international in scope, reflecting the nature of contemporary vehicle engineering.
Vehicle structure -- Friction clutch -- Manual gearboxes and overdrives -- Hydrokinetic fluid couplings and torque converters -- Semi- and fully automatic transmission -- Transmission hearings and constant velocity joints -- Final drive transmission -- Tyres -- Steering -- Suspension -- Brake system -- Air operated power brake equipment and vehicle retarders -- Vehicle refrigeration -- Vehicle body aerodynamics.
Previous ed.: London: Arnold, 1989.
Includes index.
Keywords: Motor vehicles; Motor vehicles -- Maintenance and repair; Electronic books